Pengaruh Digital Marketing, Label Halal, Dan Kualitas Produk Terhadap Keputusan Pembelian (Studi Empiris UMKM Oleh-Oleh Getuk Eco Magelang) - Devi Laeli Putri; Rochiyati Murniningsih; Mulato Santosa (Borobudur Management Review, 2022)
Since the Covid 19 pandemic occurred, SMEs in Indonesia have experienced a decline in sales, as have the Getuk Eco Magelang SMEs. To overcome this decline, SMEs continue to try to influence consumer purchasing decisions, namely through digital marketing, halal labels, and product quality. This study aims to examine the effect of digital marketing, halal labels, and product quality on purchasing decisions at the Getuk Eco Magelang. The sample used in this study is the consumer of Getuk Eco Magelang SME’s the number of respondents is 95 respondents. Sampling using accidental sampling technique. The analytical tool used in this research is multiple linear regression. The results of this study indicate that digital marketing has no effect on purchasing decisions, halal labels have a positive effect on purchasing decisions, product quality has a positive effect on purchasing decisions.